Kajian Etnosains Pada Potensi Penggunaan Saliva untuk Penyembuhan Luka Ringan di Lampung - Silvia Nur Azizah; Mustajib Mustajib; Ahsanul Buduri Agustiar; Hafidha Asni Akmalia (Al-Hayat: Journal of Biology and Applied Biology, 2021)
Traditional medicine is the local wisdom of the Indonesian people. The people of the Jaya Sakti area of Central Lampung use saliva as a medicine to heal minor wounds. This study aims to determine the potential use of saliva in healing minor wounds. This study uses the method of observing the community. The results showed that based on the percentage of data from field observations related to the use of saliva for minor injuries in communities around Jayasakti village, Anak Tuha District, Central Lampung Regency, it is known that most people have used saliva to treat minor wounds, while other communities have never used it. or seeing other people use saliva as a remedy for minor wounds. Based on the literature review, the content contained in saliva, especially histatin, plays a major role in improving wound healing by increasing the revitalization phase, especially through increasing keratinocyte migration and proliferation. Besides, people use saliva as a medicine to heal minor wounds because they follow the habits of people who have been passed down from generation to generation and already know the content of saliva that can heal minor wounds, namely histatin and alkaline acids. In conclusion, saliva is effective to use as a wound-healing drug because of the compounds contained in saliva and people's experiences when using it.